Simulation of Polymer Crystallization under Isothermal and Temperature Gradient Conditions Using Particle Level Set Method - Zhijun Liu; Jie Ouyang; Chunlei Ruan; Qingsheng Liu (Crystals, 2016)
Morphological models for polymer crystallization under isothermal and temperature gradient conditions with a particle level set method are proposed. In these models, the particle level set method is used to improve the accuracy in studying crystal interaction. The predicted development of crystallinity during crystallization under quiescent isothermal condition by our model is reanalyzed with the Avrami model, and good agreement between the predicted and theoretical values is observed. In the temperature gradient, the computer simulation results with our model are consistent with the experiment results in the literature.